2015
DOI: 10.1039/c5dt02685g
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic ferrichrome: structural motifs for switching between narrow- and broad-spectrum activities in P. putida and E. coli

Abstract: A series of novel ferrichrome (FC) analogs was designed based on the X-ray structure of FC in the FhuA transporter of Escherichia coli. Two strategies were employed: the first strategy optimized the overall size and relative orientation of H-bonding interactions. The second strategy increased H-bonding interactions by introducing external H-donors onto analogs' backbone. Tris-amino templates were coupled to succinic or aspartic acid, and the second carboxyl was used for hydroxamate construction. Succinic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 67 publications
4
24
0
Order By: Relevance
“…For each ligand, the protonation constants were assigned by comparing them with the known protonation constants of hydroxamate ligands. 24 , 35 , 37 , 42 When the changes in temperature, ionic strength, and ligand structures are allowed for, the protonation constants of H 3 L1 and H 4 L2 are in excellent agreement with the literature values of the cyclic hydroxamate siderophore DFOE (log K 1 = 9.89, log K 2 = 9.42, and log K 3 = 8.65) reported by Anderegg et al 37 The pH-dependent UV–vis titrations of H 3 L1 and H 4 L2 ( Figure S1 ) revealed the development of a strong band with λ max = 230 nm, when the pH was increased from 7 to 11, which is usually observed for a hydroxamic group deprotonation process. 24 , 43 The amino group protonation of H 4 L2 was not detectable in the experimental pH range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each ligand, the protonation constants were assigned by comparing them with the known protonation constants of hydroxamate ligands. 24 , 35 , 37 , 42 When the changes in temperature, ionic strength, and ligand structures are allowed for, the protonation constants of H 3 L1 and H 4 L2 are in excellent agreement with the literature values of the cyclic hydroxamate siderophore DFOE (log K 1 = 9.89, log K 2 = 9.42, and log K 3 = 8.65) reported by Anderegg et al 37 The pH-dependent UV–vis titrations of H 3 L1 and H 4 L2 ( Figure S1 ) revealed the development of a strong band with λ max = 230 nm, when the pH was increased from 7 to 11, which is usually observed for a hydroxamic group deprotonation process. 24 , 43 The amino group protonation of H 4 L2 was not detectable in the experimental pH range.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the physicochemical properties of Zr(IV) complexes with three further trihydroxamic ligands, i.e. H 3 L3 (FOXE 2-5), 38 H 3 L4 (T4), 35 and DFOE ( Scheme 1 ), were also investigated for the sake of comparison. The ligands employed here were selected to investigate the influence of some structural elements on the physicochemical properties of Zr(IV) complexes: i.e., (i) the number of binding groups required to complete the coordination sphere of the metal cation; (ii) the possible advantage of the macrocyclic effect; (iii) the size of the ligand cavity, which should be large enough to minimize ring strain; (iv) the symmetry of the ligand, which could limit the probability of a complex challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Although enantiomers of β‐amino acid, tripods 3 and 5 , display a distinct chirality pattern around the iron, for γ‐amino acid analogue 4 at the same concentration only a trace signal was observed in the ligand‐to‐metal charge transfer (LMCT) region of the iron complex (data not shown) . Such decrease in chiral preference around the iron with increasing linker length has been previously observed in transition from α to β oriented hydroxamates as well . The chiral center of β and γ amino acids is decoupled from the hydroxamates by one or two methylene spacers.…”
Section: Resultsmentioning
confidence: 62%
“…Thus, replacing α‐amino acid hydroxamates with their β and γ equivalents tackles both complementary approaches simultaneously: introducing polar substituents for enhanced hydrogen bonding to the transporter, yet moving them further away from the metal‐binding site. A recent example of analogues with β positioned hydroxamates indicates a significant potential of this approach …”
Section: Introductionmentioning
confidence: 99%
“…The m / z values obtained in MS experiments were successfully employed by our research group on numerous occasions. 52 , 53 A few major peaks characterized the MS spectra of the investigated solutions of the Fe(ClO 4 ) 3 /ligand and Ga(ClO 4 ) 3 /ligand with a 1:1 ratio ( Figure S2 ). The peaks were attributed to the mononuclear species ( Table S2 , Table S3 ), and no peaks corresponding to the free ligand were present.…”
Section: Results and Discussionmentioning
confidence: 99%